Rational Identification of a Colorectal Cancer Targeting Peptide through Phage Display - Ferreira, D (2019)
Colorectal cancer is frequently diagnosed at an advanced stage due to the absence of early clinical indicators. Hence, the identification of new targeting molecules is crucial for an early detection and development of targeted therapies. This study aimed to identify and characterize novel peptides specific for the colorectal cancer cell line RKO using a phage-displayed peptide library. After four rounds of selection plus a negative step with normal colorectal cells, CCD-841-CoN, there was an obvious phage enrichment that specifically bound to RKO cells. Cell-based enzyme-linked immunosorbent assay (ELISA) was performed to assess the most specific peptides leading to the selection of the peptide sequence CPKSNNGVC. Through fluorescence microscopy and cytometry, the synthetic peptide RKOpep was shown to specifically bind to RKO cells, as well as to other human colorectal cancer cells including Caco-2, HCT 116 and HCT-15, but not to the normal non-cancer cells. Moreover, it was shown that RKOpep specifically targeted human colorectal cancer cell tissues. A bioinformatics analysis suggested that the RKOpep targets the monocarboxylate transporter 1, which has been implicated in colorectal cancer progression and prognosis, proven through gene knockdown approaches and shown by immunocytochemistry co-localization studies. The peptide herein identified can be a potential candidate for targeted therapies for colorectal cancer.